IMPACT OF INTERPRETATION HAZARD MAP OF RIAU ISLANDS, MALACCA STRAIT APPLICATIONS WITH GIS - Beny Bastiawan; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 1998)
Geographic information systems can generate a map that is very useful for handlingthe information systems danger of pollution due to oil spills. Whether in the form of amap that presents only the basic data to map the character to live life. By using theframework of thought and the flow concept done on this concept, other areasconsidered vulnerable to the dangers of oil spills can be mapped. Besides, if there arefuture incidents in the area of study, provided the location of the incident is knownwith certainty, then the same concept can be mapped area which affected the earliest.